Forest recovery in the karst region of Puerto Rico - Rivera, L. W.; Mitchell Aide, T.
Widespread deforestation has led to an increase in secondary forest in the tropics. During the late 1940s in Puerto Rico, forest covered only 6
Keywords: ABANDONED COFFEE PLANTATIONS; ABANDONED PASTURES; SECONDARY FOREST; TROPICS